2014
DOI: 10.1111/eff.12198
|View full text |Cite
|
Sign up to set email alerts
|

Multiple watershed alterations influence fish community structure in Great Plains prairie streams

Abstract: Stream fish distributions are commonly linked to environmental disturbances affecting terrestrial landscapes. In Great Plains prairie streams, the independent and interactive effects of watershed impoundments and land cover changes remain poorly understood despite their prevalence and assumed contribution to declining stream fish diversity. We used structural equation models and fish community samples from third‐order streams in the Kansas River and Arkansas River basins of Kansas, USA to test the simultaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…Relative to other studies that have documented temporal changes in fish community structure due to human disturbance(Geheber & Piller, 2012;Gido et al, 2010;Morgan & Cushman, 2005;Perkin et al, 2014), our study area has been less altered and demonstrates moderate landscape-scale disturbances can have negative effects on stream fish communities after several decades. Fish community composition shifted in the Saline River basin across three time periods possibly in response similar combinations of functional traits through time.In the Ouachita Headwaters basin, there was no shift in fish community composition in multivariate space, but taxonomic dissimilarity decreased, whereas functional dissimilarity did not change as evidenced by homogeneity of group dispersions.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…Relative to other studies that have documented temporal changes in fish community structure due to human disturbance(Geheber & Piller, 2012;Gido et al, 2010;Morgan & Cushman, 2005;Perkin et al, 2014), our study area has been less altered and demonstrates moderate landscape-scale disturbances can have negative effects on stream fish communities after several decades. Fish community composition shifted in the Saline River basin across three time periods possibly in response similar combinations of functional traits through time.In the Ouachita Headwaters basin, there was no shift in fish community composition in multivariate space, but taxonomic dissimilarity decreased, whereas functional dissimilarity did not change as evidenced by homogeneity of group dispersions.…”
mentioning
confidence: 57%
“…The response of fish communities to landscape alterations is highly variable due to the covariation of natural and anthropogenic gradients, multi-scale mechanisms, nonlinear responses and land use legacies (Allan, 2004). Utilisation of historical datasets with adequate spatial extent is critical to assess temporal shifts in fish community composition (Geheber & Piller, 2012;Gido et al, 2010), especially after watershed alteration (Morgan & Cushman, 2005;Perkin et al, 2014) that can result in gradual or abrupt changes (Gido et al, 2010;Matthews, Marsh-Matthews, Cashner, & Gelwick, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…At the other end of the land‐use gradient, southern redbelly dace ( Chrosomus erythrogaster (Rafinesque, 1820)) and blacknose dace ( Rhinichthys atratulus (Hermann, 1804)) were most abundant at the site with the greatest fish diversity across all time periods and the lowest level of urban development. Both of these species have shown sensitivity to urban land development in other regions (Fraker, Snodgrass, & Morgan, ; Long & Schorr, ; Perkin et al, ). From this case study it is clear that broad‐scale and catchment‐wide assessments of assemblage change do not capture finer‐scale or spatially structured changes, and multi‐scale investigations stand a better chance of identifying the most appropriate spatial scales for assessing assemblage and species status (Fausch et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Results (see below) suggested that H differed through time, and thus H patterns were plotted for 1976 and 2016. Diversity change maps were overlain onto maps of land development change because terrestrial land development is an agent of change for fish assemblages, including contributing to the loss of fish diversity (Perkin, Troia, Shaw, Gerken, & Gido, ; Wang et al, ). Historical land use for the years 1974 and 2012 were acquired from Falcone ().…”
Section: Methodsmentioning
confidence: 99%
“…Habitat dimension can be measured as stream width (m) and depth (m), whereas heterogeneity involves structures such as aquatic vegetation, canopy cover, and instream woody structure. Each of these components of habitat is regulated by hydrologic processes that link streams to terrestrial landscapes (Burcher, Valett, & Benfield, 2007;Perkin, Troia, Shaw, Gerken, & Gido, 2016). For example, terrestrial habitat transformation has disrupted historic vegetative succession regimes and allowed for woody encroachment across basins (Briggs et al, 2005), and this affects stream reaches and segments by stabilising banks, increasing stream depths, closing otherwise open canopies, and depositing instream woody structure (Fischer et al, 2010;Poff et al, 1997).…”
Section: Introductionmentioning
confidence: 99%